2019
DOI: 10.3390/nu11040809
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hydration in Clinical Conditions: Indirect and Direct Approaches Using Bioimpedance

Abstract: Although the need to assess hydration is well recognized, laboratory tests and clinical impressions are impractical and lack sensitivity, respectively, to be clinically meaningful. Different approaches use bioelectrical impedance measurements to overcome some of these limitations and aid in the classification of hydration status. One indirect approach utilizes single or multiple frequency bioimpedance in regression equations and theoretical models, respectively, with anthropometric measurements to predict flui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 93 publications
(136 reference statements)
2
127
0
2
Order By: Relevance
“…The bioimpedance vector analysis (BIVA) is used in clinical and sports fields to study the change in body fluids and nutritional state [10][11][12][13]. It represents the raw bioimpendance parameters (resistance (R) and reactance (Xc)) as a point on the R-Xcgraph in which both length and slope are considered.…”
Section: Introductionmentioning
confidence: 99%
“…The bioimpedance vector analysis (BIVA) is used in clinical and sports fields to study the change in body fluids and nutritional state [10][11][12][13]. It represents the raw bioimpendance parameters (resistance (R) and reactance (Xc)) as a point on the R-Xcgraph in which both length and slope are considered.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The high rates of rehospitalization and mortality may indicate that the current guidelines for discharge, typically based on clinical assessment of volume status, are insufficient for AHF patient stabilization. 10 Daytime measures of haemodynamic parameters, such as blood pressure, left ventricular ejection fraction (LVEF), and cardiac output, are important determinants of prognosis in patients with heart failure. 11 We have previously demonstrated that daytime measures of pulsatile haemodynamics, such as carotid-femoral pulse wave velocity (CFPWV), backward (Pb) amplitude of the reflection wave, carotid pulse pressure, 12,13 and electromechanical activation time (EMAT), 9 a measure of the ventriculo-arterial coupling, were independently associated with post-discharge outcomes in patients with AHF.…”
Section: Introductionmentioning
confidence: 99%
“…There are mainly four methods of body fluid volume assessment: (a) prediction of TBW with function of single-frequency (50 kHz), (b) use of low (1–5 kHz) and high (100–500 kHz) frequencies and (c) bioimpedance spectroscopy (BIS) where a broad band of frequencies (1–1,000 kHz) is used (Low-frequency currents (<5 kHz) pass through the ECV (they cannot pass the cell membrane), while high-frequency currents pass though both ECV and intracellular volume compartments [41]. A variable amount of very low-frequency current, regardless at which frequency the current is introduced, can penetrate the membranes of muscle cells, particularly when the current is parallel to the muscle fiber [42]) and (d) bioimpedance vector measurement (BIVA), where continuous bivariate vector of impedance (resistance and reactance) is evaluated, compared with the deviation from a reference healthy population [43]. These methods can be applied segmentally or as a whole body measurement [44], while the results can be presented as absolute volumes or vector distribution [45, 46].…”
Section: Bia Techniquesmentioning
confidence: 99%
“…In general, BIS prediction equations could involve 5 different errors: impedance measurement error, regression error (standard error against the reference method), intrinsic error of the reference method, electric-volume model error (e.g., anisotropy of tissues), and biological variability of healthy and diseased subjects. On the contrary, vector analysis (BIVA) seems to engage only mainly measurement error and biological variability, as there is no need for body weight measurement and use of regression equations [43].…”
Section: Bia Techniquesmentioning
confidence: 99%